The documentation and educational centre information and informational services - Lucía Mabel Linares Bonilla; Zoraida Vera Bonet; Ania Rosa Fleites Fernández (ADIDE Federación, 2014)
This article is written by authors from Santa Clara, Cuba, that belong to the Pedagogical University "Félix Varela" and is titled: The Center for Educational Documentation and Information (CDIP) and information services, referring to work done by the CDIP, which highlights the main objective of preparing users based on them aware and know to use the resources that have been created to facilitate the search for information from the bibliography and use of new information technologies. They work at the University of Pedagogical Sciences and are responsible for selecting, acquiring, processing, store and make available to its users all the documents, audiovisual materials and technology related to education, pedagogy and other related sciences, with the aim of offer specialized information to all levels of education of the Ministry of Education, providing to all teachers and all who are interested in the educational field, the information necessary for their work pedagogical, both for development and improvement, as to investigate and solve problems in your classroom, school or community.